Abolición de la esclavitud en el Perú y su continuidad. - Rodríguez Pastor, Humberto (2005)
This essay examines Castilla’s government politic to deal the problem of black and Chinese slavery in the middle of the XIX century. Manumission, compensation, landholders and hire are analyzed during the peak of guano business to specify the true meaning of the law of freedom of slaves in 1854.